THE IMPACTS OF CREATING YOUTUBE VIDEO PROJECT TO FACILITATE STUDENTS’ CRITICAL THINKING - Dedeh Rohayati; Etika Rachmawati (University of Kuningan, 2021)
Nowadays, the education system has to meet the characteristics of 21st century skills, among others, the involvement of digital literacy, students’ centeredness, and critical thinking. This study depicts the impact of creating YouTube Video project to facilitate students’ critical thinking skill at which the qualitative case study is employed. Six third year students of English Department learning the topic of English for Medical are selected purposively. The interview questions analyzed thematically and documentation of YouTube Video processed descriptively using scoring rubric are utilized. The finding revealed that: (1) students were aware of the learning which is based on project and understand critical thinking; (2) students perceived creating YouTube video project in learning the topic of English for Medical as a tool to facilitate critical thinking skill; (3) students demonstrated their satisfactory improvement in English for Medical; and (4) students were aware of digital literacy to support their future career and lifelong learning. Meanwhile, the documentation of YouTube video shows that students’ video uploading onto YouTube were excellent in term of length, content accuracy, and presentation. Their works were weakened by their unfamiliarity of how to create an effective YouTube Video. Consequently, YouTube Video is unclear if it would be widely utilized, particularly, for those who intend to learn English for Medical. This implied that students’ critical thinking skill in creating a project needs improvement.